Molecular identification and effect of salt-tolerant plant growth-promoting rhizobacteria on the biochemical aspect and growth of rice - Chompa, Sayma Serine; Ali Tan, Kee Zuan; Amin, Adibah Mohd; Hun, Tan Geok; Ahmad Ghazali, Amir Hamzah; Sadeq, Buraq Musa; Akter, Amaily; Rahman, Md Ekhlasur; Rashid, Harun Or (Instituto de Investigaciones Agropecuarias, 2024)
Soil salinization, a rising issue globally, is a negative effect of the ever-changing climate, which has drawn attention to, and exacerbated problems related to soil degradation and the decline in wetland rice (Oryza sativa L.) production, leading to an unstable national economy. The use of rhizosphere inhabiting microorganisms (plant growth-promoting rhizobacteria, PGPR) is a viable method for boosting agricultural production on saline soils and reduce salt stress in rice crops. The objective of this study was to support the development of rice under salt stress by using a consortium of bacterial strains. ‘Pokkali’ rice plants inoculated with single Bacillus tequilensis and B. aryabhattai isolates were compared with consortium and non-inoculated plants while salinity was increased and by irrigation with tap water (control), 30 mM (5 dS m-1) and 60 mM (10 dS m-1) NaCl. The present study exhibited that inoculation of a mixed inoculum at 5 dS m-1 resulted in significantly higher dry weight of the shoots and roots of seedlings (9.29 and 1.24 g, respectively) which was due to the increased SPAD value, proline content (7.55 μmol g-1 FW), and antioxidant enzyme activity in the inoculated plants. The higher accumulation of osmoprotectants such as proline supported Na+ ion reduction and antioxidant enzymes such as ascorbate peroxidase and reduced polyphenol oxidase content protect against higher cellular damage, eventually leading to increase plant growth performance in saline soil. This study demonstrates some positive effects of the locally isolated salt tolerant consortium PGPR strains on the growth of rice plants under salt stress conditions.